A review of the potential and constraints for crossbreeding as a basis for goat production by smallholder farmers in Ethiopia - Abebe, Belete Kuraz (2023)
The purpose of this review was to provide and synthesize validated and up-to-date scientific knowledge on the benefits and drawbacks of crossbreeding as a basis for goat production by Ethiopian smallholder farmers. The majority of Ethiopian smallholder farmers and pastoralists rely on goat production for their livelihoods. Ethiopia's goat population is extensive, with eight genetically recognized indigenous goat breeds. These breeds, on the other hand, do not produce exceptionally well, and their contributions to smallholder farmers and the national economy fall far short of their complete output potential.